1999
DOI: 10.1111/j.1541-0072.1999.tb01959.x
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Development Incentives from Developer Give‐Aways: A Critical Guide for Development Practitioners and Citizens

Abstract: The vast majority of commwrities offer fuuuzcial incentives to private businesses and, among these, tax incentives remain the most widely used. Tax and other f-ial subsidies used to attract firm account for the bulk of public resources spent on economic development. Yet the interests of city residents-especially those marginalized in city politic~enerally are not a key consideration in the fashioning of incentives. Using a hypothetical abatement proposal, this article highlights nine key questions that must be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Safeguards against the overuse of fiscal incentives include contracts outlining specific goals and benefits expected from the businesses toward the host communities, and correctly assessing the benefits of incentive deals. The greatest income benefits will be realized when incentive deals are geared towards projects aimed at increasing the net wages of low-income residents (Oden & Mueller, 1999). Weber (2002) cautions against the use of subsidies and incentives to firms as gifts.…”
Section: Role Of Public Investments In Private Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Safeguards against the overuse of fiscal incentives include contracts outlining specific goals and benefits expected from the businesses toward the host communities, and correctly assessing the benefits of incentive deals. The greatest income benefits will be realized when incentive deals are geared towards projects aimed at increasing the net wages of low-income residents (Oden & Mueller, 1999). Weber (2002) cautions against the use of subsidies and incentives to firms as gifts.…”
Section: Role Of Public Investments In Private Developmentmentioning
confidence: 99%
“…While referred to by different names and designations such as empowerment zones, economic target areas and renaissance districts, property and sales tax advantages are critical incentives. Of these incentives, tax abatements are the primary tool used by governments to influence private investment (Oden & Mueller, 1999). Tax incentives come in a variety of forms that essentially give credits, exemptions or abatements on business costs.…”
Section: Role Of Public Investments In Private Developmentmentioning
confidence: 99%
“…In response to this uneven economic development, public and private actors with a vested interest in the economic health of places have become involved in growth promotion (Logan 1978;Logan and Molotch 1987;Zukin 1991). It is now common for cities and small towns to provide tax breaks, subsidies, and other incentives for firms to relocate from elsewhere or to simply remain in the area (Green, Fleischmann, and Kwong 1996;Oden and Mueller 1999). The literature on the ability of local actors to influence local economic outcomes offers mixed results.…”
Section: State-designated Enterprise Zones 509mentioning
confidence: 99%
“…Further, Humphrey and Wilkinson (1 993) found that tax incentives had no effect on net migration or property sales. However, it is tax cuts that are the most commonly employed incentive within the enterprise zone development strategy (Oden and Mueller 1999).…”
Section: Do Tax Incentives and Other Pro-growth Efforts Matter?mentioning
confidence: 99%
“…Some studies do offer regionally specific (Sands, Reese, & Kahn, 2006) or national scope (Dalehite, Mikesell, & Zorn, 2005) descriptions of the extent of municipal use of these controls, and there are discussions of the merits and problems of such controls (Oden & Mueller, 1999;Weber, 2002). Some studies do offer regionally specific (Sands, Reese, & Kahn, 2006) or national scope (Dalehite, Mikesell, & Zorn, 2005) descriptions of the extent of municipal use of these controls, and there are discussions of the merits and problems of such controls (Oden & Mueller, 1999;Weber, 2002).…”
mentioning
confidence: 99%